Human capital externalities vs. substitution effects as determinants of regional wages: Evidence from German micro data - Rasmus Thönnessen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This article reconsiders the empirical evidence on regional human capital externalities using longitudal survey data from the German Socio-Economic Panel (SOEP). It complements the empirical literature on the role of human capital for explaining regional wage differences. Based on the framework by Moretti (2004a), the impact of different proxies of regional human capital intensity on regional wages is estimated while controlling for individual productivity determinants and regional characteristics. The results are compared with the constant-composition approach by Ciccone and Peri (2006) which accounts for imperfect substitution between unskilled and skilled labor. The Mincerian panel results with level data indicate that one additional year of education has an external wage effect of 2%. However, once a difference specification is estimated, external effects are no longer present. The theoretical predictions by Ciccone and Peri (2006) that the Mincerian approach leads to an upward biased estimate cannot be verified.
Keywords: J24; R23; R11; 330